PENGARUH LITERASI KEUANGAN, HERDING, DAN HEURISTIK TERHADAP KINERJA INVESTASI MAHASISWA DI INDONESIA - Karimah, Haifa Asma; Suman, Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to analyze the influence of financial literacy, herding, and heuristics on the investment performance of university students in Indonesia. The first issue in this study is the small number of investors caused by the motivation and return of investment, and the second issue is the discovery of anomalies in the capital market. The main theory used as a reference in this research is Behavioral Finance theory. This type of research is quantitative with primary data using a Likert scale, tested by the Partial Least Square method. The results in this study indicate that financial literacy and heuristics have a positive and significant effect on investment performance. In addition, herding has a positive but insignificant influence on investment performance. This research has a contribution as a source of new information and reference in the development of science, especially with studies related to investment, capital markets, financial behavior, and other related topics.